Derecho constitucional económico: estabilidad presupuestaria y derechos sociales - Aranda Álvarez, Elviro (Revista de Derecho Político, 2017)
Resumen: La estabilidad presupuestaria y los límites a la deuda pública se han convertido en los principios referenciales de la política económica de la Unión Europea tras el paso por la crisis económica de los últimos años. La aplicación de estos principios supone hacer grandes recortes en el Estado del Bienestar que puede afectar sustancialmente a los derechos sociales e, incluso, el modelo de Estado de nuestro país. El presente artículo pretende dejar constancia que tanto la interpretación de esos principios como el nuevo artículo 135 de la CE deben ser interpretados de conformidad con las reglas económicas constitucionales que aseguran la vigencia del Estado social y democrático de Derecho. Summary: Introduction 1. Constitutional economic rules in the Spanish Constitution of 1978: the lack of a definite economic model and the diffuse reference to budget stability 2. Public spending as a key instrument in welfare state economic policies. 3. Justice principles regarding public spending contained in article 31.2 of the Spanish Constitution. 3. Budget stability in european law. evolution and goals. 4. The tense balance between economic and social rights and budget stability. Conclusions. Abstract: Budget stability and public debt limits have become key economic policy factors in the European Union in the wake of the recent economic crisis. The application of these principles involves major cuts to the Welfare State that may substantially affect social rights and even the model of State in our country. This article argues that both these principles and the new article 135 of the Spanish Constitution must be interpreted in accordance with constitutional economic rules that ensure the continuing validity of the social and democratic State based on the rule of law.